Associations between education level, blood-lipid measurements and statin treatment in a Danish primary health care population from 2000 to 2018 - Marius Mølsted Flege; Margit Kriegbaum; Henrik Løvendahl Jørgensen; Bent Struer Lind; Lise Bathum; Christen Lykkegaard Andersen; Anna Elise Engell (Taylor & Francis Group, 2023)
AbstractObjective To examine whether education level influences screening, monitoring, and treatment of hypercholesterolemia.Design Epidemiological cohort study.Setting Department of Clinical Biochemistry, Copenhagen University Hospital Hvidovre.Subjects Cholesterol blood test results ordered by general practitioners in Greater Copenhagen were retrieved from 2000-2018. Using the International Standard Classification of Education classification, the population was categorized by length of education in three groups (basic education; up to 10 years, intermediate education; 11-12 years, advanced education; 13 years or more). The database comprised 13,019,486 blood sample results from 653,903 patients.Main Outcome Measures Frequency of lipid measurement, prevalence of statin treatment, age and comorbidity at treatment initiation, total cholesterol threshold for statin treatment initiation, and achievement of treatment goal.Results The basic education group was measured more frequently (1.46% absolute percentage difference of total population measured [95% CI 0.86%-2.05%] in 2000 and 9.67% [95% CI 9.20%-10.15%] in 2018) over the period compared to the intermediate education group. The advanced education group was younger when receiving first statin prescription (1.87 years younger [95% CI 1.02-2.72] in 2000 and 1.06 years younger [95% CI 0.54-1.58 in 2018) compared to the intermediate education group. All education groups reached the treatment goals equally well when statin treatment was initiated.Conclusion Higher education was associated with earlier statin prescription, although the higher educated group was monitored less frequently. There was no difference in reaching treatment goal between the three education groups. These findings suggest patients with higher education level achieve an earlier dyslipidemia prevention intervention with an equally satisfying result compared to lower education patients.Key PointsLittle is known about the role of social inequality as a possible barrier for managing hypercholesterolemia in general practice.Increasing education level was associated to less frequent measurement and less frequent statin treatment.Patients with higher education level were younger, and less comorbidity at first statin prescription.Education level had no effect on frequency of statin treatment-initiated patients reaching the treatment goal was found.